Pressure-induced interlamellar stromal keratitis after laser in situ keratomileusis - Kruse, Friedrich; et al. (Cornea, 2011)
To describe a patient with interlamellar stromal keratitis induced by increased intraocular pressure (IOP) [Pressure-induced interlamellar stromal keratitis (PISK)] after laser in situ keratomileusis (LASIK) surgery.Case report and review of the literature.We report a case of interlamellar stromal keratitis induced by increased IOP after LASIK surgery. A 42-year-old man presented with persistent interface haze after uneventful LASIK. The patient described onset of decreased visual acuity after the first 2 postoperative weeks, failed to improve with high-dose topical steroid drops, and had significantly elevated IOP values up to 48 mm Hg. IOP was resistant to maximal topical antiglaucomatous therapy. The patient showed both improvement in visual acuity and decrease in interface haze after discontinuation of topical steroids and lowering of IOP by both topical and systemic treatment. Slit-lamp optical coherence tomography ruled out a fluid accumulation in the interface.PISK appears clinically almost identical to diffuse lamellar keratitis after LASIK. It is important to measure the IOP and be suspicious when a diffuse interface haze occurs after the first postoperative week, is resistant to or even exacerbates in response to an increase in topical steroid treatment, and is not associated with other causative events. Slit-lamp optical coherence tomography is a valuable tool that allows differentiation between space-occupying interface fluid collection and non-space-occupying interface fluid collection to avoid falsely low or normal IOP measurements in PISK.
EVALuna2:21052